Use of raw materials for development of meat semifinished products - Chernyushok, Olga; Shevchenko, Ivanna (My University, 2020)
Досліджено проблему на ринку напівфабрикатів, у зв’язку з нестачею білків та мінеральних речовин в організмі. Коротко описано вплив заморожування на зберігання напівфабрикатів. Запропоновано збагатити, за допомогою внесення до рецептури молочної сироватки збагаченої Mg та Mn. Наведено корисні речовини, які містяться у молочних білках, які запропоновано внести в рецептуру м’ясного напівфабрикату. Описано рецептуру приготування пельменів. Описано вплив даних компонентів на органолептичні показники продукту. The problem in the market of semi-finished products, due to the lack of proteins and minerals in the body, has been studied. The effect of freezing on the storage of semi-finished products is briefly described. It is proposed to enrich by adding to the recipe whey enriched with Mg and Mn. The useful substances contained in milk proteins, which are proposed to be included in the recipe of meat semi-finished products, are listed. The recipe for cooking dumplings is described. The influence of these components on the organoleptic characteristics of the product is described.
Keywords: напівфабрикати; молочна сироватка; магній; манган; м'ясо; пельмені; збагачена рецептура; meat; milkwhey; magnesium; manganese; semi-finished products; dumplings; enriched recipe; кафедра технології м’яса і м’ясних продуктів